Nasionalisasi Perusahaan-Perusahaan Asing di Aceh Timur Tahun 1945- 1968 - Halimatussa’diah Simangunsong; Suprayitno S (LP4MK STKIP PGRI Lubuklinggau, 2019)
The Aceh Timur as territorial area which have been prepared by the east Indies government as center of financial investment foreign especially Holland in plantation and mining project. Pass through, the nationalit of the Aceh Timur tried to waive Holland restless which have exploided the available nature resources, being state possession. The nationalization in Aceh Timur being the phenomenon which being buried by the DI/TII whole happen in Aceh. Eventhough, the nationalization still happened in Aceh Timur. Taking over the foreign companies which consist in the Aceh Timur until 1960 whole republic possession and using for prosperous Indonesian people eventhough Industrial sector mining project or plantation sector.